2013
DOI: 10.1002/jor.22527
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin inhibits bone healing during distraction osteogenesis

Abstract: Osteosarcoma (OS) is the most common malignant bone tumor affecting children and adolescents. Many patients are treated with a combination of chemotherapy, resection, and limb salvage protocols. Surgical reconstructions after tumor resection include structural allografts, non-cemented endoprostheses, and distraction osteogenesis (DO), which require direct bone formation. Although cisplatin (CDP) is extensively used for OS chemotherapy, the effects on bone regeneration are not well studied. The effects of CDP o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 29 publications
5
27
0
2
Order By: Relevance
“…These data confirm that CIS showed a severe impairment over differentiation and maturation of the osteoblastic lineage and justifies the lower peri‐implant bone formation, corroborating Stine et al. ().…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…These data confirm that CIS showed a severe impairment over differentiation and maturation of the osteoblastic lineage and justifies the lower peri‐implant bone formation, corroborating Stine et al. ().…”
Section: Discussionsupporting
confidence: 87%
“…As chemotherapy increases severity and accelerates the progression of experimental periodontitis (Garcia et al., ; Theodoro et al., ), clinically, exposure of these implants to plaque can lead to impairment of osseointegration due to severe peri‐implantitis. As CIS develops hazardous effect over bone repair and bone formation (Stine et al., , ), more studies are needed for proper and secure rehabilitation of patients previously submitted to chemotherapy. Moreover, circulating levels of CIS have been shown up to 20 years after therapy; thus, long‐term renal effects (Gietema et al., ; Orchard et al., ) and its impairment over bone growth can be expected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the need to maintain bone homeostasis and overall mass and strength of the skeleton during the necessary treatments to successfully kill tumour cells is critical. Indeed, several studies have indicated a lack of bone regeneration and/or healing after treatment of osteolytic metastases or following chemotherapy, which suggests that cancer cells (and specific treatments) might have altered the behaviour and/or differentiated activity of osteoclasts, osteoblasts and/or osteocytes 67,68 .…”
Section: Mechanisms Of Bone Metastasismentioning
confidence: 99%
“…Among the most recently used chemotherapeutic drugs, Cisplatin stands out because it has a marked antitumor activity against various types of cancer (Almeida et al, ; Mitin et al, ). However, one of its side effects is a reduction in bone remodeling (Al‐Mahalawy et al, ; Kovács, ; Matheus et al, ; Stine et al, ; Young, Shih, et al, ; Young, Virolainen, et al, ), which may hamper the patients' bone metabolism and, consequently, impair their rehabilitation with osseointegratable implants. Thus, this study assessed the bone quality and the osseointegration of dental implants after exposure to the chemotherapeutic drug Cisplatin.…”
Section: Discussionmentioning
confidence: 99%